Large-scale continuous preparation of highly stable α-CsPbI3/m-SiO2 nanocomposites by a microfluidics reactor for solid state lighting application. Issue 21 (23rd May 2022) - Guo, Runze; Liu, Yufeng; Fang, Yongzheng; Liu, Zhifu; Dong, Langping; Wang, Lei; Li, Wenyao; Hou, Jingshan
Abstract : CsPbI3 -Mesoporous SiO2 nanocomposites with ultrahigh chemical stability were fabricated by the microfluidic technology for large-scale continuous production. Abstract : CsPbI3 has the least chemical stability among the CsPbX3 (X = Cl, Br, and I) perovskite nanocrystal (PNC) family due to its thermodynamically metastable characteristics, thus limiting the development of all-inorganic perovskite white-light devices. The current study presents a microfluidic-based continuous large-scale fabrication of CsPbI3 -mesoporous SiO2 (CPI/m-SiO2 ) nanocomposites to solve the problem of large-scale continuous production of stable, repeatable, high-quality perovskite NCs. The results reveal that the chemical stability and thermal quenching behaviour of CPI PNCs were greatly improved due to the protection of mesoporous silica. Particularly, the water resistance property of CPI/m-SiO2 nanocomposites improved two-fold compared to that of noncomposite CPI PNCs, and the thermal stability of the CPI/m-SiO2 nanocomposites improved nearly three-fold at 373 K when compared with that of the noncomposite CPI NCs. Furthermore, photons were speculated to transmit along with the pores and channel structure of m-SiO2 to reduce photon absorption between NCs. Moreover, the microfluidic technology can operate continuously and is precisely controllable, enabling large-scale nanocomposite synthesis with uniform size and shape.